2020
DOI: 10.21203/rs.3.rs-23941/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep learning vs. atlas-based models for fast auto-segmentation of the masticatory muscles on head and neck CT images

Abstract: Background: Impaired function of masticatory muscles will lead to trismus. Routine delineation of these muscles during planning may improve dose tracking and facilitate dose reduction resulting in decreased radiation-related trismus. This study aimed to compare a deep learning model with a commercial atlas-based model for fast auto-segmentation of the masticatory muscles on head and neck computed tomography (CT) images. Material and methods: Paired masseter (M), temporalis (T), medial and lateral pterygoid (MP… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Assessing inter‐observer variability is always challenging, because of the difficulties in defining references. This problem can be addressed in different ways, for example, by performing two‐by‐two comparisons 20 , 21 , 22 or by designating one set of contours as the reference. 19 , 23 In this study, we applied the STAPLE finalization algorithm 24 to the contours outlined by all ROs, to define a reference set (Ref) used as the shared gold standard.…”
Section: Methodsmentioning
confidence: 99%
“…Assessing inter‐observer variability is always challenging, because of the difficulties in defining references. This problem can be addressed in different ways, for example, by performing two‐by‐two comparisons 20 , 21 , 22 or by designating one set of contours as the reference. 19 , 23 In this study, we applied the STAPLE finalization algorithm 24 to the contours outlined by all ROs, to define a reference set (Ref) used as the shared gold standard.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, convolutional neural networks (CNN) have shown encouraging results in human organ segmentation. Several studies have demonstrated that deep learning-based segmentation yielded more consistent and more accurate results than atlas-based methods for clinical images 21 , 22 . It also outperformed the atlas-based methods in terms of speed 23 .…”
Section: Introductionmentioning
confidence: 99%
“…However, atlas‐based auto‐segmentation uses a fixed size. Hence, this limits its ability to adapt to the difference in patient anatomy 9 …”
Section: Introductionmentioning
confidence: 99%
“…Hence, this limits its ability to adapt to the difference in patient anatomy. 9 Artificial intelligence (AI)-based methods have recently been proposed for the segmentation required for treatment planning. AI-based algorithms can perform highly intensive computations.…”
Section: Introductionmentioning
confidence: 99%